Dynamic behavior of superconducting flux qubit excited by the series of electromagnetic pulses - Kiyko, A.S.; Omelyanchouk, A.N.; Shevchenko, S.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
We study theoretically the behavior of the superconducting flux qubit subjected to the series of the electromagnetic pulses. The possibility of controlling the system state via changing the parameters of the pulse is studied. We calculated the phase shift in the tank circuit weakly coupled to the qubit which can be measured by the impedance measurement technique. For the flux qubit we consider the possibility to estimate relaxation rate from the impedance measurements by varying the delay time between the pulses.